2007
DOI: 10.1212/01.wnl.0000257090.01107.2f
|View full text |Cite
|
Sign up to set email alerts
|

Decreased frontal choline and neuropsychological performance in preclinical Huntington disease

Abstract: As choline-containing compounds relate to membrane turnover, membrane dysfunction antedating neuronal death is suggested to occur in the frontal cortex in preclinical carriers of Huntington disease. This dysfunction may be responsible for some of the neuropsychological deficits observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 37 publications
4
43
0
Order By: Relevance
“…H magnetic resonance spectroscopy (MRS) has previously been evaluated as a biomarker modality in premanifest and early HD. [4][5][6][7][8][9][10][11] However, the literature is conflicted with regard to the utility of metabolites such as total N-acetylaspartate (tNAA), a measure of neuronal integ-*These authors contributed equally to this work. References e1-e7 are available on the Neurology Web site at www.neurology.org.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…H magnetic resonance spectroscopy (MRS) has previously been evaluated as a biomarker modality in premanifest and early HD. [4][5][6][7][8][9][10][11] However, the literature is conflicted with regard to the utility of metabolites such as total N-acetylaspartate (tNAA), a measure of neuronal integ-*These authors contributed equally to this work. References e1-e7 are available on the Neurology Web site at www.neurology.org.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] However, the literature is conflicted with regard to the utility of metabolites such as total N-acetylaspartate (tNAA), a measure of neuronal integ-rity, 12 as potential biomarkers in HD. In an attempt to address these discrepant findings, arising in part from small subject numbers, poorly comparable outcome measures and heterogeneity within patient cohorts, we sought to determine the potential of MRS as an HD biomarker using large numbers of subjects in defined, homogeneous clinical cohorts and examined MRS outcome measures normalized to unsuppressed water rather than metabolites such as total creatine (tCr) which are affected in HD.…”
mentioning
confidence: 99%
“…Cho/Cr ratios correlated positively with scores of neuropsychological testing in the elderly population 18,21 and in patients with preclinical Huntington disease. 34 In the latter, investigators have suggested that a decrease in Cho indicates a reduction of myelin membrane turnover that precedes neuronal death that may be responsible for the neuropsychological deficits. 34 Thus, a postoperative decrease in the Cho/Cr ratio as well as a postoperative decrease in the NAA/Cr ratio may imply neuronal damage caused by CEA, thereby resulting in postoperative cognitive impairment.…”
Section: Figmentioning
confidence: 99%
“…34 In the latter, investigators have suggested that a decrease in Cho indicates a reduction of myelin membrane turnover that precedes neuronal death that may be responsible for the neuropsychological deficits. 34 Thus, a postoperative decrease in the Cho/Cr ratio as well as a postoperative decrease in the NAA/Cr ratio may imply neuronal damage caused by CEA, thereby resulting in postoperative cognitive impairment. On the other hand, the univariate analyses showed that the ⌬Cho/Cr ratio in the cerebral hemisphere ipsilateral to the operative site was significantly higher in patients with postoperatively improved cognition than in those with postoperatively unchanged or impaired cognition, though the multivariate analysis did not demonstrate a significant difference.…”
Section: Figmentioning
confidence: 99%
“…However, several studies have also used two-dimensional chemical shift imaging (2D-CSI) [33,40,41]. Studies measuring changes by MRS revealed different values of metabolite concentrations in patients with HD [34,35,42,43]. Recently, several longitudinal clinical studies have been performed.…”
Section: Magnetic Resonance Imaging (Mri) and Spectroscopy (Mrs)mentioning
confidence: 99%